Effect Of Ga3 And Row Ratio On Floral Traits Of Component Lines Of BRRI Hybrid Dhan2 (Bangladesh Journal of Agricultural Research, 2013)
Component lines (A and R lines) of BRRI hybrid dhan2 were assessed under treatment of GA3 application and row ratio on days to 5% and 50% flowering, duration of opening of floret, angle of open floret, filament length, anther length, stigma length, panicle exsertion rate, stigma exsertion rate and outcrossing rate. The CMS line viz; BRRI 10A have been found to be usable female parents for hybrid rice seed production due to their stigma length, stigma exsertion rate, duration of blooming, anther length and filament length. The different between genotypic and phenotypic variation was not remarkable for most of the characters studied indicating negligible environmental influence on the traits. The maximum duration of opening of floret (158.10 min) and angle of floret opening (28.870) were obtained with the application of 350 g GA3 ha-1. The improvement in the floral traits with increased GA3 level might be due to increased availability of GA3 which enhanced floral traits. The CMS line can be used as potential female parent in hybrid rice seed production of BRRI hybrid dhan2. Bangladesh J. Agril. Res. 38(1): 155-163, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15202